Quadriceps muscle strength, radiographic knee osteoarthritis and knee pain: the ROAD study. Issue 1 (December 2015) - Muraki, Shigeyuki; Akune, Toru; Teraguchi, Masatoshi; Kagotani, Ryohei; Asai, Yoshiki; Yoshida, Munehito; Tokimura, Fumiaki; Tanaka, Sakae; Oka, Hiroyuki; Kawaguchi, Hiroshi; Nakamura, Kozo; Yoshimura, Noriko
Abstract Background The objective of this study was to clarify the association of quadriceps muscle strength with knee pain using a large-scale, population-based cohort of the Research on Osteoarthritis/osteoporosis Against Disability (ROAD) study. Methods From the 2566 subjects at the third visit of the ROAD study, the present study analyzed 2152 subjects who completed radiographic examinations and measurements of muscle strength and mass (690 men and 1462 women; mean age, 71.6 ± 12.2 years). Knee pain was assessed by an experienced orthopedist. Knee osteoarthritis (OA) was defined according to Kellgren-Lawrence (KL) grade. Quadriceps muscle strength and muscle mass at the lower limbs were measured by the Quadriceps Training Machine (QTM-05F, Alcare Co., Ltd. Tokyo, Japan) and the Body Composition Analyzer MC-190 (Tanita Corp., Tokyo, Japan), respectively. Results Quadriceps muscle strength and weight bearing index (WBI: quadriceps muscle strength by weight) were significantly associated with knee pain after adjustment for age and body mass index, whereas grip strength and muscle mass at the lower limbs were not. The significant association of quadriceps muscle strength with knee pain was independent of radiographic knee OA. Conclusion The present cross-sectional study showed an independent association of quadriceps muscle strength with knee pain.